2011
DOI: 10.1523/jneurosci.3454-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

The Neurophysiology and Pathology of Brain Zinc

Abstract: Our understanding of the roles played by zinc in the physiological and pathological functioning of the brain is rapidly expanding. The increased availability of genetically modified animal models, selective zinc-sensitive fluorescent probes, and novel chelators is producing a remarkable body of exciting new data that clearly establishes this metal ion as a key modulator of intracellular and intercellular neuronal signaling. In this Mini-Symposium, we will review and discuss the most recent findings that link z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
244
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(253 citation statements)
references
References 112 publications
(142 reference statements)
6
244
0
3
Order By: Relevance
“…Studies support that vitamin E and selegiline could slow or stop Mild Cognitive Impairment (MCI) to moderate/severe NCD conversion (8,9). Zinc is an element that has widespread function within neurons, including binding to metal-binding proteins, and the modulation of presynaptic, synaptic, and postsynaptic neurotransmitter receptors, such as Nmethyl-d-aspartate and Gamma-aminobutyric acid (10)(11)(12). Therefore, the homeostasis of zinc has a critical role in the maintenance of normal cellular processing.…”
Section: Introductionmentioning
confidence: 99%
“…Studies support that vitamin E and selegiline could slow or stop Mild Cognitive Impairment (MCI) to moderate/severe NCD conversion (8,9). Zinc is an element that has widespread function within neurons, including binding to metal-binding proteins, and the modulation of presynaptic, synaptic, and postsynaptic neurotransmitter receptors, such as Nmethyl-d-aspartate and Gamma-aminobutyric acid (10)(11)(12). Therefore, the homeostasis of zinc has a critical role in the maintenance of normal cellular processing.…”
Section: Introductionmentioning
confidence: 99%
“…Although most biological zinc ions are tightly associated with proteins (1), pools of loosely bound or "mobile" forms (2) serve regulatory or signaling functions (3), including nucleation of protein self-assembly (4), triggering of signaling pathways (5), and modification of cellular metabolism (6). In this capacity, mobile zinc performs essential tasks in the physiology of the central nervous system, pancreas, and prostate (5,7,8).…”
mentioning
confidence: 99%
“…Indeed, Ca 2+ deregulation has been associated with a variety of detrimental processes in neurons, including mitochondrial dysfunction (2), generation of reactive oxygen species (3), and activation of apoptotic signaling cascades (4). More recently, zinc, a metal crucial for proper cellular functioning (5), has been found to be closely linked to many of the injurious conditions in which Ca 2+ had been thought to play a prominent role (6)(7)(8)(9)(10). In fact, it has been suggested that a number of deleterious properties initially attributed to Ca 2+ may have significant Zn 2+ -mediated components (11,12).…”
mentioning
confidence: 99%